2021
DOI: 10.1021/acsami.0c17326
|View full text |Cite
|
Sign up to set email alerts
|

Oxi-Redox Selective Breast Cancer Treatment: An In Vitro Study of Theranostic In-Based Oxide Nanoparticles for Controlled Generation or Prevention of Oxidative Stress

Abstract: capability towards anatomical contrast enhancement. These results suggest that the synthesized ITO NPs have the potential to be a novel selective therapeutic agent with a multimodal imaging property for anticancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…A H 2 DCFDA probe was employed to study the change in ROS concentration [ 188 ]. The results of this study show a decrease in ROS level at a concentration of 0.05 mM of La +3 [ 157 ]. Wang et al reported the ROS scavenging mechanism and protection effect against oxidative stress in soybean seeds [ 189 ].…”
Section: Oxygen-deficient Lanthanum Oxidementioning
confidence: 96%
See 4 more Smart Citations
“…A H 2 DCFDA probe was employed to study the change in ROS concentration [ 188 ]. The results of this study show a decrease in ROS level at a concentration of 0.05 mM of La +3 [ 157 ]. Wang et al reported the ROS scavenging mechanism and protection effect against oxidative stress in soybean seeds [ 189 ].…”
Section: Oxygen-deficient Lanthanum Oxidementioning
confidence: 96%
“…In many studies, ITO was reported as a substrate layer with other metal oxide NPs (such as ZnO, Au, Ag, Pt, Ni, Fe 2 O 3 NPs) for the development of biosensors for a range of biomedical applications [ 156 ]. Recently, ITO NPs have been reported by Hsu et al as theranostic agents for the treatment of cancer, Figure 10 [ 157 ]. Oxygen-deficient ITO NPs were prepared by the chemical precipitation method, followed by calcination at 400 °C [ 157 ].…”
Section: Indium Tin Oxide (Ito) Nanostructure In the Biological Fieldmentioning
confidence: 99%
See 3 more Smart Citations